Growth and characterization of Piperine (PPN) single crystal grown by slow evaporation solution growth technique. (7th June 2019) - Muthuraja, A.; Subramaniyan @ Raja, R.; Bharath, D.
Abstract: An organic single crystal Piperine (PPN) was grown by slow evaporation solution growth technique (SEST). Single crystal X-ray diffraction measurements were carried out on grown piperine single crystals. The crystal system was identified and lattice parameters were measured from the powder X-ray diffraction (PXRD) measurement. The transmittance of the grown crystal and cut off wavelength were analysed using UV–vis NIR studies and the cut-off wavelength was found to be 387 nm. Vickers micro hardness analysis was carried out to identify the mechanical stability of the grown crystal. Chemical etching study was carried out using different etchants and the etch pit density (EPD) was calculated. The third order nonlinear optical property of PPN crystal was studied using Z-scan technique with He–Ne laser (632·8 nm).